ACCUMULATION OF LEAD AND COPPER IN THE SEDIMENTS IN SOUTH KALIH AND PANJANG ISLAND, BANTEN: AKUMULASI TIMBAL DAN TEMBAGA PADA SEDIMEN DI PERAIRAN PULAU KALIH SELATAN DAN PULAU PANJANG, BANTEN - Nazwasyawinka, Keyla; Nurjanah, Siti; Abrar, Camelia Batun; Amalia Nasution, Isra; Dida, Eki Naidania; Sasongko, Agung Setyo; Cahyadi, Ferry Dwi; Cahyarini, Sri Yudawati (Jurnal Teknologi Perikanan dan Kelautan, 2025)
South Kalih and Panjang Islands are located in Banten Bay, small island with environmental conditions adjacent to the center of industrial activities. Industrial activities near the waters can increase the risk of heavy metal pollution, thereby affecting the quality of the aquatic environment. This study aims to evaluate the condition of aquatic environmental quality based on heavy metal content in sediments. Sediment sampling was conducted at ten observation stations using a purposive random sampling method. Heavy metal analysis was performed using the Flame Atomic Absorption Spectrometry (FAAS). The results indicate that South Kalih Island accumulated more Pb heavy metals with an average of 2.7922 mg kg⁻¹, while the highest accumulation of Cu heavy metals was on Panjang Island with an average of 5.7188 mg kg⁻¹. The accumulation of heavy metals Pb and Cu in the sediments in South Kalih and Panjang Island was below the standard threshold, except at PPS5P1 of Panjang Island, where Cu concentrations exceeded the CCME (2002) quality guideline. Areas with dense anthropogenic activities are more likely to increase the accumulation of heavy metals in the waters.